Mobile robot navigation system vision based through indoor corridors - Mohd Shah, Hairol Nizam; Lee, Zhong Zhen; Kamis, Zalina; Ahmad, Azhar; Baharon, Mohd Rizuan (IJENS Publisher, 2019)
Nowadays, industry has been moving toward fourth industry revolution, but surveillance industry is still using human in patrol. This will put this industry in risk due to human nature instincts. By using a mobile robot with assist of vision sensor to patrol can bring this industry to a new level. However, the indoor corridor navigation will become a big challenge to this method. The objective of this project is to develop a navigation system using vision sensor and navigate the mobile robot in indoor corridor environment. To perform this operation, a control system though the WLAN communication develop to guide the movement of mobile robot. Besides that, corridor following system with vision sensor that using Sobel edge detection method and Hough transform to getting the vanish point is needed to help the robot to safely travel in the corridor. Both systems can be using MATLAB to be execute and link with the mobile robot through WLAN connection. This system can be analysis the corridor condition base on different feature and can decide to drive the mobile car in the direction that given. The image capture by mobile robot can be stream to MATLAB in real time and receive a feedback in short time.